THE DEVELOPMENT OF KARAKUL BREEDING CLUSTERS: INNOVATIVE APPROACHES AND ECONOMIC EFFICIENCY ANALYSIS - Shodiyev Bekzod Tulkinovich; Abdieva Dilfuza Kurbanovna (Modern American Journals, 2025)
This article analyzes the development prospects of Karakul sheep breeding clusters in Uzbekistan. It examines the key factors necessary for the effective functioning of these clusters, including pasture utilization, the introduction of innovative technologies, and economic efficiency. A SWOT analysis is conducted to assess the strengths and weaknesses of the cluster model, as well as its opportunities and threats. Based on the research findings, recommendations are proposed for further development of Karakul sheep breeding.
Keywords: Karakul sheep breeding, cluster, pasture, innovation, economic efficiency, SWOT analysis, investment.